Innovation in traditional porcelain company G. Benedikt - Janáková, Julie (2023)
This thesis recognizes the importance of innovation in an everchanging world, even for traditional companies. The aim of this thesis is to gain a comprehensive understanding of the factors that influence product innovation at G. Benedikt and identify trends and factors within the HoReCa sector that can help the company to remain competitive and profitable in the future. To achieve this author elaborated on the s the company’s approach towards innovation, evaluated the impact of being a family business on its innovativeness, explored the external factors, assessed how is G. Benedikt compared to its competitors in terms of innovation and market trends that may affect the development of new products. Additionally, the research seeks to uncover potential areas of focus and opportunities for further innovation to drive growth and maintain a competitive edge within the industry.